HATE SPEECH ON SOCIAL MEDIA AGAINST HALLE BAILEY “THE LITTLE MERMAID” - Alfirah, Syarifa; Nasta, Mardiyanah; Nurfadhilah, Auliyanti Sahril (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This research aims to analyze the types of hate speech and the dominant types of hate speech on social media against actress Halle Bailey who played the character Ariel in the movie The Little Mermaid on social media using Mainack Mondal's theory (2017). The researcher used descriptive qualitative method as an approach. The data source of this research are Instagram and Twitter platforms. The results of this study found five types of hate speech that are physical, behavior, racial, ethnicity, and social class. Physical and racial which were the most widely used of all cases.